Effect of calcium and fluoride addition to hydrogen peroxide bleaching gel on tooth diffusion, color, and microhardness - Torres, Carlos R.G. [UNESP]; Zanatta, Rayssa Ferreira [UNESP]; Silva, Tatiane Josefa [UNESP]; Borges, Alessandra B. [UNESP] (Operative Dentistry, 2019)
Objectives: The aim of this study was to evaluate the effect of calcium and fluoride addition to a 35% hydrogen peroxide (HP) bleaching gel with regard to its diffusion through the tooth structure, enamel microhardness, and bleaching efficacy. Methods and Materials: Eighty specimens (6 mm in diameter and 2 mm in height; 1 mm/ enamel and 1 mm/dentin) were obtained from bovine incisors that were polished and divided into four groups (n=20) according to the remineralizing agent added to the gel: Ca = 0.5% calcium gluconate; F = 0.2% sodium fluoride; Ca+F = 0.5% calcium gluconate and 0.2% sodium fluoride; and control = no agent. Initial microhardness and color were assessed. The samples were positioned over simulated pulpal chambers filled with acetate buffer solution to capture the HP. Gels were applied over enamel for 30 minutes, and HP diffusion was assessed by spectrophotometry two hours after bleaching. Microhardness was measured immediately after bleaching and then the specimens were immersed into artificial saliva for seven days for final color assessment. Data were analyzed by one-way analysis of variance followed by Tukey test. Results: Bleaching reduced microhardness for all groups (p=0.0001), but the Ca+F and F groups showed lower reductions after bleaching. The addition of Ca, F, and Ca+F decreased the peroxide penetration through the tooth structure (p=0.0001), but there were no differences in color change for DL (p=0.357), Da (p=0.061), Db (p=0.823), and DE (p=0.581). Conclusion: The addition of calcium and fluoride in the gel did not affect bleaching efficacy, but it was able to reduce both the peroxide diffusion and the bleached enamel microhardness loss.